PENGARUH EFEK PERSISTENSI LABA DALAM ANALISIS FUNDAMENTAL GUNA MEMPREDIKSI RETURN SAHAM - IRWANTO HANDOJO (Media Bisnis, 2014)
Quirin and Allen (2000) found that the fundamental analysis to be something very important when corporate profits are transitory and become something less important when the amount of profit the company is permanent. To that end, fundamental analysis to be something very relevant when the condition of the company showed earnings unstable (there is no persistence of earnings). This study continues Quirin and Allen (2000) to see if indeed there is a persistence of earnings effects that need to be considered in the fundamental analysis to predict price (return) shares and whether this effect is consistent in every industry sector to cases in Indonesian capital market. Using data from 34 public companies and analyzed using multiple regression it was found that the persistence of earnings is an important factor that should be included in research on the influence of fundamental factors on share returns and also that the testing of the influence of fundamental factors on share returns should be in the context of long-term.